Results of conservative treatment of periodontitis in destructive forms (LLC "Endo Press", 2020)
Elimination of chronic lesions of odontogenous infection is a high priority in endodontic practice. This article deals with the conservative treatment of chronic periodontitis in the acute stage. Two clinical cases are presented with a detailed description of the methods of treatment and the results. Positive results confirmed clinically and radiographically after three years. These observations show that the use of the preparation on the basis of calcium hydroxide «Metapaste» in the treatment of acute stage of chronic periodontitis by delayed filling enhances the possibilities of conservative treatment of periodontitis